The Rao-Blackwellized Particle Filter: A Filter Bank Implementation. (6th December 2010) - Hendeby, Gustaf; Karlsson, Rickard; Gustafsson, Fredrik
Abstract : For computational efficiency, it is important to utilize model structure in particle filtering. One of the most important cases occurs when there exists a linear Gaussian substructure, which can be efficiently handled by Kalman filters. This is the standard formulation of the Rao-Blackwellized particle filter (RBPF). This contribution suggests an alternative formulation of this well-known result that facilitates reuse of standard filtering components and which is also suitable for object-oriented programming. Our RBPF formulation can be seen as a Kalman filter bank with stochastic branching and pruning.